Little Miss Magic - Hargreaves, Roger (World international Limited, 1991)
From Mr Tickle's extraordinarily long arms to Little Miss Princess's sparkly crown, the Mr Men and Little Misses have been delighting children for generations with their charming and funny antics.
Keywords: Juvenile Fiction-Book